2021
DOI: 10.3390/diagnostics11030450
|View full text |Cite
|
Sign up to set email alerts
|

Neurogenic Thoracic Outlet Syndrome with Supraclavicular Release: Long-Term Outcome without Rib Resection

Abstract: Our aim was to define clinical long-term outcome of surgery for neurogenic thoracic outlet syndrome without rib resection, and to find factors predicting long-term results. For the 94 patients, the main outcomes were pain, numbness, weakness, and upper-extremity function. The Quick Disabilities of the Arm, Shoulder and Hand (QuickDASH) survey, the Cervical-Brachial Symptom Questionnaire (CBSQ), and a numerical rating system served as functional outcome measures. Mean follow-up was 12.9 years. Preoperative pain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 31 publications
1
6
0
Order By: Relevance
“…All the patients fulfilled the criteria established by the Consortium for Research and Education on thoracic outlet syndrome [ 7 , 14 ]. Mean age, sex-ratio and symptoms duration of our patients were also similar to those in previous studies [ 7 , 10 , 28 ] and strength measurements on the symptomatic sides of our patients were comparable to those of Ruopsa et al recently published [ 34 ]. Electrodiagnostic testing was abnormal in 15% of our patients, certainly due to the lack of systematic evaluation of the conduction velocity in the medial antebrachial cutaneous nerve, which is reported to correlate well with a clinical diagnosis of NTOS [ 35 ].We showed that patients with NTOS had a significant strength deficit of the grip and the key pinch of 30% and 19.5% on the symptomatic sides, respectively, compared to healthy controls.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…All the patients fulfilled the criteria established by the Consortium for Research and Education on thoracic outlet syndrome [ 7 , 14 ]. Mean age, sex-ratio and symptoms duration of our patients were also similar to those in previous studies [ 7 , 10 , 28 ] and strength measurements on the symptomatic sides of our patients were comparable to those of Ruopsa et al recently published [ 34 ]. Electrodiagnostic testing was abnormal in 15% of our patients, certainly due to the lack of systematic evaluation of the conduction velocity in the medial antebrachial cutaneous nerve, which is reported to correlate well with a clinical diagnosis of NTOS [ 35 ].We showed that patients with NTOS had a significant strength deficit of the grip and the key pinch of 30% and 19.5% on the symptomatic sides, respectively, compared to healthy controls.…”
Section: Discussionsupporting
confidence: 91%
“…Particularly, it would be interesting to assess the efficiency of our specific rehabilitation program or other management modalities concerning strength improvement and symptoms relief. In fact, strength assessment seems very helpful to point out upper-limb weakness during the diagnostic process [ 14 ], and certainly during the follow-up to monitor the efficiency of treatments as previously shown after surgical procedure [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Rehabilitation programs may target strength evolution more specifically during the follow-up of patients with NTOS to assess if muscular strengthening could improve upper-limb function. Moreover, the upper-limb strength and endurance assessment could be an interesting parameter to monitor the impact of the rehabilitation program or the surgical management on weakness [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…Cross-sectional data on 67 consecutive patients undergoing surgery for NTOS between 1997 and 2011 came from patient records (Ruopsa et al 2021). All the operations were performed by a single surgeon (M.V.)…”
Section: Methodsmentioning
confidence: 99%
“…We calculated also BMI, because some authors have evaluated the influence of body weight on technical and functional outcomes of surgical treatment for NTOS (Maqbool et al 2019;Mattox et al 2016;Ohman et al 2018). We also were interested in this topic (Ruopsa et al 2021). Symptom duration we calculated as years from symptom onset until surgery (Table 2).…”
Section: Methodsmentioning
confidence: 99%